The Makassar Annals - Cummings, William (dfd58f59-c451-4283-b058-d32ab8ab46de, 2011)
The Makassar annals Translated and edited by William Cummings Beginning in the 1630s, a series of annalists at the main courts of Makassar began keeping records with dated entries that recorded a wide variety of specific historical information about a wide variety of topics, including the births and deaths of notable individuals, the actions of rulers, the spread of Islam, trade and diplomacy, the built environment, ritual activity, warfare, internal political struggles, social and kinship relations, eclipses and comets, and more. These Lontaraq bilang were a clear departure in form and function from the genealogically-structured chronicles being composed about the ruling families of Gowa and Talloq in the same era. By the end of 1751, nearly 2400 entries had been completed. These records are a rich lode of information for scholars interested in virtually any aspect of life in premodern Makassar, and are a rare and precious resource for scholars of Southeast Asia. This is the first English translation and annotation of the annals. William Cummings is an associate professor of history at the University of South Florida. He is the author of Making blood white; Historical transformation in early modern Makassar, A chain of kings; The Makassarese chronicles of Gowa and Talloq, and numerous articles about Makassarese history and culture.